PERAN GURU PENDIDIKAN AGAMA ISLAM DALAM MENGATASI DAMPAK NEGATIF TIKTOK PADA SISWA DI MTsN 15 JOMBANG - Chafizd, Miftachul; Anshori, Sholihul (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, Indonesia, 2025)
Abstract: The rapid advancement of information technology, especially through social media platforms such as TikTok, has had a significant impact on adolescents in the field of education. TikTok, in addition to functioning as a source of entertainment, can also have negative influences, such as reducing students' learning motivation, encouraging them to imitate trends that are contrary to moral values, and changing their behavior. This research aims to explore the role of Islamic Religious Education teachers in addressing the negative impacts of TikTok usage among students at MTsN 15 Jombang. The study employs a qualitative approach with a case study design. The findings reveal that Islamic Religious Education teachers take on multiple roles, including as educators, mentors, counselors, and role models in helping students overcome the negative impacts of TikTok. These roles are reflected through efforts to create a religious school environment, provide guidance both inside and outside the classroom, and adjust teaching methods to align with technological developments, so that they are more relevant and accessible to students who are highly involved with digital media.